Pengaruh Workload, Masa Perikatan Audit dan Spesialisasi Auditor Terhadap Defisiensi Audit pada KAP yang digunakan oleh Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2015-2018 - I Gusti Ayu Diah Utari; Ketut Tanti Kustina; Putu Gitta Gresia (Universitas Warmadewa, 2021)
The Effect Of Workload, Audit Tenure, And Auditors’ Specialization On Audit Deficiencies Based On Audit Firms Used By Manufacture Companies That Listed On IDX 2015-2018 This study aims to examine whether workload, audit tenure, auditors’ specialization influence the occurrence of audit deficiencies conducted by audit firms on the basis of the data that collected by the Finance Finance Professions Supervisory Centre (PPPK), Ministry of Finance RI. This research uses 40 audit firms as population and 34 sample that was collected by purposive sampling method. Workload is measured by the ratio of comparison between total clients and total audit partners. Audit tenure calculated using intervale scale. Auditors’ specialization calculated by dummy variable. Basis of the data of audit deficiencies is based on report of audit results by the Finance Finance Professions Supervisory Centre (PPPK), Ministry of Finance RI. This research is quantitative research using multiple linear regression analysis. The results indicate that the workload and audit tenure has a positive impact on audit deficiencies. Auditors’ specialization has a negative impact on deficiencies audit.